Using Taylor series expression, find a power series solution for the equation
2x2d2y/dx2-xdy/dx+(x-5)y=0 in powers of (x-1) if y(1)=4 and y'(1)=2
Solution;
Taylors series expansion of f(x) at x=a is given as follows;
"f(x)=f(a)+f'(a)(x-a)+\\frac{f''(a)}{2!}(x-a)^2+\\frac{f'''(a)}{3!}(x-a)^3+..."
Given;x=1
We have;
"f(x)=f(1)+f'(1)(x-1)+\\frac{f''(1)}{2!}(x-1)^2+\\frac{f'''(1)}{3!}(x-1)+..."
Since;
y(1)=4
y'(1)=2
Also;
"2x^2\\frac{d^2y}{dx^2}-x\\frac{dy}{dx}+(x-5)y=0"
By direct substitution;
"2(1^2)y''-1(2)+(1-5)(4)=0"
"2y''-2-16=0"
"y''(1)=9"
Now we find the triple derivative at x=1;
"2x^2\\frac{d^2y}{dx^2}-x\\frac{dy}{dx}+(x-5)y=0"
Factorise to obtain;
"2x^2\\frac{d^2y}{dx^2}-x\\frac{dy}{dx}+xy-5y=0"
Differentiate by applying the product rule;
"[2x^2\\frac{d^3y}{dx^3}+\\frac{d^2y}{dx^2}(4x)]-[x\\frac{d^2y}{dx^2}+\\frac{dy}{dx}]+[x\\frac{dy}{dx}+y]-0=0"
By direct substitution;
"2(1^2)y'''+(9)(4\u00d71)-(1)(9)-2+(1)(2)+4=0"
Simplify to obtaining;
"y'''(1)=-\\frac{31}{2}"
Hence we have the power solution series as;
"f(x)=4+2(x-1)+\\frac9{2!}(x-1)^2-\\frac{31}{2\u00d73!}(x-1)^3+..."
Simplify;
"f(x)=4+2(x-1)+\\frac92(x-1)^2-\\frac{31}{12}(x-1)^3+..."
Comments
Leave a comment